Gentrification in Amsterdam: Assessing the Importance of Context. Issue 8 (24th April 2014) - Hochstenbach, Cody; Musterd, Sako; Teernstra, Annalies
Abstract: This paper investigates the income levels and income developments of in‐migrating, out‐migrating, and sitting households in gentrifying neighbourhoods in Amsterdam over a 10‐year period (1999–2008). First, to analyse these data, this paper discusses the impact of institutional and housing market contexts on the residential‐mobility patterns of households and subsequently discusses the outcomes of gentrification processes. The general Continental‐European context and the specific context of Amsterdam are highlighted in particular. We argue that in highly regulated markets, marginal gentrification can form an important process of neighbourhood upgrading. This contrasts the gentrification stage model. Second, using a unique, individual‐level longitudinal dataset, we show that gentrifying neighbourhoods in Amsterdam arguably form cases of marginal gentrification. Recent in‐migrants possess incomes that are structurally lower than the incomes of sitting residents. However, in‐migrants experience significant incumbent upgrading after moving in, more so than the sitting population. The Amsterdam housing market, dominated by social‐rental housing, is key to explaining these mobility patterns. Yet, a gradual liberalisation of the social‐rental stock could arguably contribute to more mature forms of gentrification. Copyright © 2014 John Wiley & Sons, Ltd.